2009
DOI: 10.1002/asi.21179
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive economy and satisficing in information seeking: A longitudinal study of undergraduate information behavior

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 37 publications
2
72
0
1
Order By: Relevance
“…The one-stop-shop experience RDS offer meets the observed changes in users' information seeking behaviours. Amongst those changes is the fact that students are indicating a marked preference towards using search engines and the Internet to source information for their academic endeavours (Warwick et al, 2009). In addition, the single search box, emulating the search engine experience, brings a new dimension to information searching via library portals, bringing down the walls between library collections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The one-stop-shop experience RDS offer meets the observed changes in users' information seeking behaviours. Amongst those changes is the fact that students are indicating a marked preference towards using search engines and the Internet to source information for their academic endeavours (Warwick et al, 2009). In addition, the single search box, emulating the search engine experience, brings a new dimension to information searching via library portals, bringing down the walls between library collections.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do electronic resources offer greater accessibility than printed resources, but they also offer greater currency, particularly with the development of online publishing ahead of print. In their longitudinal study of undergraduate students, Warwick, Rimmer, Blandford, Gow, and Buchanan (2009) have shown that students have a marked preference towards using the Internet to source information for the academic task at hand rather than using the varied and complex range of library resources. Moreover, students exhibit 'strategic satisficing' behaviours (Warwick et al, 2009), whereby they tend to reproduce known and successful information searching strategies (i.e.…”
Section: Because Of Their Ease Of Use and Quick Delivery Of 'Good Enomentioning
confidence: 99%
See 2 more Smart Citations
“…As such, past research supports the use of Camtasia as a data collection tool within qualitative interviews discussing computer-based activities (i.e. website utilization, webbased programs) (Barmby et al 2009;Lim 2002;Qiu et al 2007;Warwick et al 2009). To date, however, few researchers have used Camtasia to aid in conducting cognitive interviews, and those that have utilized the software in this capacity, mainly employed the recording features to capture the "think aloud" component of cognitive interviewing, or to record the audio, while playbacks of captured video are reviewed with research participants (Lim 2002;Qiu et al 2007;Willson and Given 2010).…”
Section: Improving Instrument Pretesting With Camtasiamentioning
confidence: 95%